Strategi Pemanfaatan Lahan Gambut melalui Pengembangan Agroforestri Kopi Liberika (Coffea liberica) - D. Mawardhi, Andre; Setiadi, Doni (Seminar Nasional Lahan Suboptimal, 2018)
Mawardhi et al, 2019.Â Strategy on Peatland Utilisaton through Development of Coffea Liberica Agroforestry. pp. 43-51.Agriculture development in Indonesia has been shifted from fertile land to suboptimal land, as example peatland. Area covered by peatland in Indonesia are approximately 14,9 million ha, which about 52% of the land are potentially for agriculture. There is limitation for farmer to cultivate various crop because of peat soil characteristic which less support for plant growth. Coffea liberica is one of plantation comodity which can survive and productive in peatland, so that it recomended as main comodity in peatland region. Farmers in Jambi, Riau, and South Sumatera have been developed coffea liberica agroforestry on peatland. Its product sold to local market and other countries, such as Malaysia and Singapore. Coffea liberica production should be increased to meet market demand. Coffea liberica development supported by internal strength i.e. a) planting material supply, b) labour, and c) land farming; and opportunity i.e. a) market information access and b) coffee product price. In other hand, technology competence is a weakness that limited coffee farming. Technology inputs on coffee liberica include recomended variety, population management, fertilisation, pruning, pest and disease control, and drainage control. Those aspects showed that development model of coffee liberica agroforesty based on technology was the appropriate strategy of peatland utilisation on plantation.